Species turnover (β‐diversity) in ectomycorrhizal fungi linked to NH4+ uptake capacity. Issue 23 (24th November 2015) - Kranabetter, J. M.; Hawkins, B. J.; Jones, M. D.; Robbins, S.; Dyer, T.; Li, T.
Abstract: Ectomycorrhizal (EcM) fungal communities may be shaped by both deterministic and stochastic processes, potentially influencing ecosystem development and function. We evaluated community assembly processes for EcM fungi of Pseudotsuga menziesii among 12 sites up to 400 km apart in southwest British Columbia (Canada) by investigating species turnover (β‐diversity) in relation to soil nitrogen (N) availability and physical distance. We then examined functional traits for an N‐related niche by quantifying net fluxes of NH 4 +, NO 3 − and protons on excised root tips from three contrasting sites using a microelectrode ion flux measurement system. EcM fungal communities were well aligned with soil N availability and pH, with no effect of site proximity (distance–decay curve) on species assemblages. Species turnover was significant (β1/2  = 1.48) along soil N gradients, with many more Tomentella species on high N than low N soils, in contrast to Cortinarius species. Ammonium uptake was greatest in the spring on the medium and rich sites and averaged over 190 nmol/m 2 /s for Tomentella species. The lowest uptake rates of NH 4 + were by nonmycorrhizal roots of axenically grown seedlings (10 nmol/m 2 /s), followed by Cortinarius species (60 nmol/m 2 /s). EcM roots from all sites displayed only marginal uptake of nitrate (8.3 nmol/m 2 /s). These results suggest NH 4 + uptake capacity is an important functional trait influencing the assembly of EcM fungal communities. The diversity of EcM fungal species across the region arguably provides critical belowground adaptations to organic and inorganic N supply that are integral to temperate rainforest ecology.